The Transformation of the Wayang Figures in the Serat Damarwulan Manuscript - Mochtar Lutfi (MOZAIK HUMANIORA, 2020)
This study aims to reveal the elements that experience the process of cultural transformation and the meaning illustrated through the illustrations of wayang figures in the Serat Damarwulan Manuscript. In this study, descriptive qualitative methods are used, namely placing words or sentences in a logical structure to explain concepts in the relationships between existing elements. Furthermore the data in the form of a sign system will provide a more comprehensive understanding. Transformation of wayang characters is a transition or change that occurs in the surface structure of a set of symbols of figures in wayang to become figures that are likened to or equated with characters in Serat Damarwulan, while the structure in the puppet characters themselves has not changed. The results of this study indicate that the elements undergoing cultural transformation in addition to scripts and languages are also illustrations that show the character of wayang characters in the characters contained in the Serat Damarwulan Manuscript. Knight figures such as Ronggolawe and Damarwulan are portrayed as Bima and Arjuna characters. While evil figures like Menakjinggo are portrayed as giants. These figures give meaning in the Serat Damarwulan, but in their own way the characters remain or do not change. This shows that the Serat Damarwulan Manuscript describes the process of cultural transformation in the form of puppet characters from Hindu-Buddhist to Islam that goes peacefully by not changing the main character, storyline, or background.